Cumulative Effect of Annual Additions of Uncomposted Oak and Maple Leaves on the Yield of Vegetables. Issue 2 (3rd April 2018) - Maynard, Abigail A.
ABSTRACT: For 22 years, plots were amended annually with oak ( Quercus velutina Lam.) or sugar maple leaves ( Acer saccharum Marsh.) in Mt. Carmel, CT on a loamy upland soil. Leaves were incorporated into the soil immediately after application in the fall. Yields of 12 different vegetable crops (lettuce, peppers, eggplant, tomatoes, edamame, delicata squash, spaghetti squash, onions, leeks, rutabaga, carrots, and beans) from these plots were compared to yields from unamended controls. All plots received equal amounts of fertilizer. There were no significant differences in vegetable yields with any of the crops between any of the treatments indicating there are no deleterious effects of annual applications of uncomposted leaves. Some soil characteristics such as organic matter and pH improved on the leaf amended plots. Study shows that annual applications of leaves to cropland (sheet composting) is a viable alternative for the disposal of leaves.